The effect of Active Learning in the Style of Small Groups in Developing Some Motor Abilities and Learning the Skill of Peaceful Correction with Basketball for Students - Rashad Tareq Yousef (Institute of Medico-legal Publications Pvt Ltd, 2021)
The aim of the current study is to identify the effect of learning the active method for small groups indeveloping some motor skills and learning the skill of peaceful correction for basketball students. Theresearcher believes that learning the skill of peaceful archery requires the teacher to apply it. The methodsof dealing with students ’thinking and their reliance on self-learning affect positively and effectively inlearning this skill, and for this the research community is identified and students represent the first stage ofthe College of Physical Education and Sports Sciences, Dhi Qar University. An academic year (2018-2019)with a total of 100 students, 30 students were selected randomly by lot, and they were divided into twogroups, one experimental p. (15) students, an applied educational curriculum prepared by the researcher bylearning to adopt small groups of type B Active in developing some motor abilities and learning the skill ofpeaceful association, the basketball department for a period of (4) weeks, at a rate of two educational unitsper week, and the second supervising the number of (15) students representing Division (E). The methodfollowed by the subject teacher was used, and after several procedures the researcher concluded that theeducational curriculum prepared by e, which was applied to the members of the experimental group, had animpact on the development of motor abilities and the level of skill performance.